TRP Channels in Human Prostate - Carl Van Haute; Dirk De Ridder; Bernd Nilius (The Scientific World Journal)
This review gives an overview of morphological and functional characteristics in the human prostate. It will focus on the current knowledge about transient receptor potential (TRP) channels expressed in the human prostate, and their putative role in normal physiology and prostate carcinogenesis. Controversial data regarding the expression pattern and the potential impact of TRP channels in prostate function, and their involvement in prostate cancer and other prostate diseases, will be discussed.